MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK MENCARI PASANGAN PADA PELAJARAN IPS KELAS IV SD - Juara, Fitri (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2021)
The purpose of this study is to improve student learning outcomes. with the cooperative learning model of the technique of finding a partner in the fourth grade of SD Negeri 1 Lipu, South Buton Regency. This research is a qualitative research (field research) and the subject of this research is the fourth grade students of SD Negeri 1 Lipu, totaling 21 students. The object of this research is student learning outcomes with cooperative learning techniques to find a partner. The results of this study indicate that before applying cooperative learning techniques to find partners in social studies lessons, 8 (38%) were completed and 13 (61.9%) were incomplete and the class average was 63.80. However, after learning by using cooperative learning techniques to find partners in social studies lessons in cycle I and cycle II, data obtained that student learning outcomes increased. The learning outcomes of the first cycle stated that as many as 14 (66.6%) were completed and 7 (33.3%) were not completed and the average value was 70. Then the results of the second cycle test showed 18 (81.9%) were completed and 3 (14 ,2%) has not been completed and the average grade is 76. Thus, it can be concluded that cooperative learning techniques to find a partner can improve the learning outcomes of fourth grade students of SD Negeri 1 Lipu, South Buton Regency.